AquaNet - Chemical parameters from Erssjön AquaNet platform, 2017-06-20–2017-09-25 - Skogaryd Research Catchment (University of Gothenburg, 2020)
Data contains chemical parameters from grab samples taken from the AquaNet mesocosms.
Skogaryd Research Catchment (2020). AquaNet - Chemical parameters from Erssjön AquaNet platform, 2017-06-20–2017-09-25 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/MRqDh3TUn4eG4E9YSXetRJ-G
Keywords: SITES; Chlorophyll; Fish; Nitrogen Compounds; Phosphorous Compounds; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap